2007
DOI: 10.1161/circulationaha.106.675587
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Dose-Related Effects of Aspirin on Platelet Function

Abstract: Background-The antiplatelet effect of aspirin is attributed to platelet cyclooxygenase-1 inhibition. Controversy exists on the prevalence of platelet resistance to aspirin in patients with coronary artery disease and effects of aspirin dose on inhibition. Our primary aim was to determine the degree of platelet aspirin responsiveness in patients, as measured by commonly used methods, and to study the relation of aspirin dose to platelet inhibition. Methods and Results-We prospectively studied the effect of aspi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
102
2
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 376 publications
(111 citation statements)
references
References 28 publications
6
102
2
1
Order By: Relevance
“…Conversely, there was a dose-dependent inhibition of platelet function as assessed by non-COX-1 pathways because aspirin at doses of 162 mg and 325 mg was more effective at reducing ADP-and collagen-mediated aggregation as well at prolonging CT as measured by PFA-100 than 81 mg of aspirin. 74 This interplay between COX-1-dependent and ADP-dependent pathways was also described by Frelinger et al, 6 who showed that residual arachidonic acid-induced platelet activation was less in patients taking clopidogrel, an ADP receptor antagonist, compared to controls. Adjunctive clopidogrel, in addition to low-dose aspirin, has been shown to be more effective at inhibiting platelet aggregation to ADP or collagen than high-dose aspirin (300 mg) monotherapy in diabetic patients with coronary artery disease who were resistant to low-dose aspirin.…”
Section: Post-coronary Artery Bypass Graft Surgerysupporting
confidence: 52%
See 1 more Smart Citation
“…Conversely, there was a dose-dependent inhibition of platelet function as assessed by non-COX-1 pathways because aspirin at doses of 162 mg and 325 mg was more effective at reducing ADP-and collagen-mediated aggregation as well at prolonging CT as measured by PFA-100 than 81 mg of aspirin. 74 This interplay between COX-1-dependent and ADP-dependent pathways was also described by Frelinger et al, 6 who showed that residual arachidonic acid-induced platelet activation was less in patients taking clopidogrel, an ADP receptor antagonist, compared to controls. Adjunctive clopidogrel, in addition to low-dose aspirin, has been shown to be more effective at inhibiting platelet aggregation to ADP or collagen than high-dose aspirin (300 mg) monotherapy in diabetic patients with coronary artery disease who were resistant to low-dose aspirin.…”
Section: Post-coronary Artery Bypass Graft Surgerysupporting
confidence: 52%
“…It appears that the dose-dependent effect of aspirin in aspirin-resistant patients may be mediated by non-COX-1 pathways. Gurbel et al 74 showed that aspirin at doses of 81 mg, 162 mg, and 325 mg all had near total inhibition of arachidonic acid-induced platelet aggregation with no difference seen among dose. Conversely, there was a dose-dependent inhibition of platelet function as assessed by non-COX-1 pathways because aspirin at doses of 162 mg and 325 mg was more effective at reducing ADP-and collagen-mediated aggregation as well at prolonging CT as measured by PFA-100 than 81 mg of aspirin.…”
Section: Post-coronary Artery Bypass Graft Surgerymentioning
confidence: 99%
“…10 In this double-blind, double-crossover investigation of 3 commonly used ASA doses (81, 162, and 325 mg/d), arachidonic acid-induced aggregation was suppressed in a dose-independent fashion whereas collagen-induced platelet aggregation and shear-induced platelet aggregation were significantly affected by dose. Moreover, the prevalence of resistance measured by COX-1 nonspecific methods such as ADP-, collagen-and shear-induced aggregation, was also significantly affected by dose.…”
Section: Aspirinmentioning
confidence: 92%
“…Aspirin acetylates COX and blocks the metabolism of arachidonic acid (an omega 6 polyunsaturated fatty acid) into a variety of proinflammatory and thrombosis-enhancing mediators including thromboxane [32][33][34][35] . The omega 3 fatty acids EPA and DHA compete with arachidonic acid for the same COX pathways and can also inhibit the production of inflammatory mediators.…”
Section: Potential Benefits Of Translating Knowledge To Improve Humanmentioning
confidence: 99%